Grafting molecular cobalt-oxo cubane catalyst on polymeric carbon nitride for efficient photocatalytic water oxidation - Zhen, Wenlong (2020)
In this work, we have successfully constructed a cobalt-oxo (CoIII4 O4 ) cubane complex on polymeric carbon nitride (PCN) through pyridine linkage. The covalently grafted CoIII4 O4 cubane units were uniformly distributed on the PCN surface. The product exhibited greatly enhanced photocatalytic activities for water oxidation under visible-light irradiation. Further characterizations and spectroscopic analyses revealed that the grafted CoIII4 O4 cubane units could effectively capture the photogenerated holes from excited PCN, lower the overpotential of oxygen evolution reaction (OER), and serve as efficient catalysts to promote the multi-electron water oxidation process. This work provides new insight into the future development of efficient photocatalysts by grafting molecular catalysts for artificial photosynthesis.